Exploring Bioequivalence of Dexketoprofen Trometamol Drug Products with the Gastrointestinal Simulator (GIS) and Precipitation Pathways Analyses - Marival Bermejo; Gislaine Kuminek; Jozef Al-Gousous; Alejandro Ruiz-Picazo; Yasuhiro Tsume; Alfredo Garcia-Arieta; Isabel González-Alvarez; Bart Hens; Gregory E. Amidon; Nair Rodriguez-Hornedo; Gordon L. Amidon; Deanna Mudie (Pharmaceutics, 2019)
The present work aimed to explain the differences in oral performance in fasted humans who were categorized into groups based on the three different drug product formulations of dexketoprofen trometamol (DKT) salt—Using a combination of in vitro techniques and pharmacokinetic analysis. The non-bioequivalence (non-BE) tablet group achieved higher plasma Cmax and area under the curve (AUC) than the reference and BE tablets groups, with only one difference in tablet composition, which was the presence of calcium monohydrogen phosphate, an alkalinizing excipient, in the tablet core of the non-BE formulation. Concentration profiles determined using a gastrointestinal simulator (GIS) apparatus designed with 0.01 N hydrochloric acid and 34 mM sodium chloride as the gastric medium and fasted state simulated intestinal fluids (FaSSIF-v1) as the intestinal medium showed a faster rate and a higher extent of dissolution of the non-BE product compared to the BE and reference products. These in vitro profiles mirrored the fraction doses absorbed in vivo obtained from deconvoluted plasma concentration–time profiles. However, when sodium chloride was not included in the gastric medium and phosphate buffer without bile salts and phospholipids were used as the intestinal medium, the three products exhibited nearly identical concentration profiles. Microscopic examination of DKT salt dissolution in the gastric medium containing sodium chloride identified that when calcium phosphate was present, the DKT dissolved without conversion to the less soluble free acid, which was consistent with the higher drug exposure of the non-BE formulation. In the absence of calcium phosphate, however, dexketoprofen trometamol salt dissolution began with a nano-phase formation that grew to a liquid–liquid phase separation (LLPS) and formed the less soluble free acid crystals. This phenomenon was dependent on the salt/excipient concentrations and the presence of free acid crystals in the salt phase. This work demonstrated the importance of excipients and purity of salt phase on the evolution and rate of salt disproportionation pathways. Moreover, the presented data clearly showed the usefulness of the GIS apparatus as a discriminating tool that could highlight the differences in formulation behavior when utilizing physiologically-relevant media and experimental conditions in combination with microscopy imaging.